GUGATAN GANTI KERUGIAN OLEH KELOMPOK PERWAKILAN MASYARAKAT DALAM PENEGAKAN HUKUM LINGKUNGAN - Arya Utama, I Made (Bumi Lestari; Vol 5 No 2, 2012)
Private Sanction in the form of compensation is represent one of the instrumentto be applied in the effort protection of environment sustainable and its function. Thisobligation is in line with polluter pays principle which is developed in EnvironmentalLaw. Compensation as a sanction can be requested by someone and also a group ofsociety directly and also delegation either by or outside of judicial jurisdiction. In thecase of society suing through class action, there are some conditions which must befulfilled which in practice still met some legal and unlegal constraint.
Keywords: law enforcement, class action, compensation